The Role of Public Institutions for Innovation Support in Brazil - Cláudia Brito Silva Cirani; Carlos Mamori Kono; André Moraes dos Santos; Adalberto Ramos Cassia (BBR: Brazilian Business Review)
The aim of this study was to present a brief description of the main public instruments for innovation support in Brazil. We also show a preliminary assessment of the use of these instrument s in innovativ e companies. W e conducted a two - step analysis. In the first part we conducted a quantitative descriptive analysis of historical series about resources allocat ion available by FINEP. In the second part we performed a qualitative in - depth analy sis of six companies that used the financial benefits offered by FINEP and BNDES to support innovative projects. The responses of the interviews were used to identify the perception of the attractiveness of public instruments for innovation support and pos sible limitations to their use, while other information was used to present the main public instruments for innovation s timulus in Brazil. T he results showed that the investigated companies are interested in using the instruments; however, they face diffic ulties for their adoption, due to excessive bureaucracy, high costs of innovation, and legal i nsecurity.